ARHGEF19 interacts with BRAF to activate MAPK signaling during the tumorigenesis of non‐small cell lung cancer. Issue 7 (4th December 2017) - Li, Yingchang; Ye, Zhihua; Chen, Shuai; Pan, Zhiwen; Zhou, Qianghua; Li, Yi‐Zhuo; Shuai, Wen‐di; Kuang, Chun‐Mei; Peng, Qi‐Hua; Shi, Wei; Mao, Xueli; Liu, Ran‐Yi; et al.
Abstract : Rho guanine nucleotide exchange factors (RhoGEFs) are proteins that activate Rho GTPases in response to extracellular stimuli and regulate various biologic processes. ARHGEF19, one of RhoGEFs, was reported to activate RhoA in the Wnt‐PCP pathway controlling convergent extension in Xenopus gastrulation. The goal of our study was to identify the role and molecular mechanisms of ARHGEF19 in the tumorigenesis of non‐small cell lung cancer (NSCLC). ARHGEF19 expression was significantly elevated in NSCLC tissues, and ARHGEF19 levels were significantly associated with lymph node status, distant metastasis and TNM stage; Patients with high ARHGEF19 levels had poor overall survival (OS) and progression‐free survival (PFS). Our investigations revealed that ARHGEF19 overexpression promoted the cell proliferation, invasion and metastasis of lung cancer cells, whereas knockdown of this gene inhibited these processes. Mechanistically, ARHGEF19 activated the mitogen‐activated protein kinase (MAPK) pathway in a RhoA‐independent manner: ARHGEF19 interacted with BRAF and facilitated the phosphorylation of its downstream kinase MEK1/2; both the Dbl homology (DH) and Pleckstrin homology (PH) domains of ARHGEF19 were indispensable for the phosphorylation of MEK1/2. Furthermore, downregulation of miR‐29b was likely responsible for the increased expression of ARHGEF19 in lung cancer tissues and, consequently, the abnormal activation of MAPK signaling. These findings suggest that ARHGEF19 upregulation, due to the low expression of miR‐29 in NSCLC tissues, may play a crucial role in NSCLC tumorigenesis by activating MAPK signaling. ARHGEF19 could serve as a negative prognostic marker as well as a therapeutic target for NSCLC patients. Abstract : What's new? Proteins known as Rho guanine nucleotide exchange factors (RhoGEFs) serve an important role in helping to regulate cell activities in response to extracellular stimuli. The RhoGEF family includes ARHGEF19, the function of which is uncertain. The authors of the present study examined the role of ARHGEF19 in the tumorigenesis of non‐small cell lung cancer (NSCLC). ARHGEF19 levels were elevated in NSCLC tissues and were associated with disease stage and survival. ARHGEF19 was found to activate the MAPK/ERK pathway via interaction with BRAF, suggesting an oncogenic role in NSCLC. In lung cancer tissues, ARHGEF19 upregulation was linked to miR‐29s downregulation.